Pediatric myositis ossificans mimicking osteosarcoma. Issue 5 (19th August 2015) - Yamaga, Kensaku; Kobayashi, Eisuke; Kubota, Daisuke; Setsu, Nokitaka; Tanaka, Yuya; Minami, Yusuke; Tanzawa, Yoshikazu; Nakatani, Fumihiko; Kawai, Akira; Chuman, Hirokazu
Abstract: Myositis ossificans (MO) is a rare benign cause of heterotopic bone formation in soft tissue that most commonly affects young adults, typically following trauma. We report the case of an 11‐year‐old girl who developed MO mimicking osteosarcoma in her right shoulder. Plain radiography and computed tomography showed poorly defined flocculated densities in the soft tissue and a periosteal reaction along the proximal humerus. On magnetic resonance imaging, the mass displayed an ill‐defined margin and inhomogeneous signal change. Histologically, the mass had a pseudosarcomatous appearance. Based on these findings, the patient was initially misdiagnosed with osteosarcoma at another hospital. The diagnosis was difficult because the patient was 11 years old and had no trauma history, with atypical radiographic changes and a predilection for the site of origin for osteosarcomas. We finally made the correct diagnosis of MO by carefully reviewing and reflecting on the pathological differences between stages.